Behind the words: Exploring speech acts in “The Aesop for Children” - Naela Hidayatul Mukaromah; Amalia Rosaline; Rika Setyawati (Researcher and Lecturer Society, 2025)
This study analyzed speech acts in selected fables from the website “The Aesop for Children” to explore how utterances convey meaning and moral values. Utilizing the speech act theories of John L. Austin and John R. Searle, the research examined locutionary, illocutionary, and perlocutionary acts within four fables: “The Gnat and The Bull”, “The Plane Tree”, “The Fox and The Goat”, and “The Cock and The Fox”. The findings reveal that most speech acts are directive, emphasizing the influence of utterances on the interlocutors. The moral lessons derived from these fables highlight the importance of humility, gratitude, caution, and the consequences of deception. This research underscores the significance of understanding speech acts in children’s literature, providing insights for parents and educators in guiding children’s reading experiences. Future studies could expand the scope by analyzing a larger corpus of fables from diverse cultural backgrounds to compare how speech acts function across different storytelling traditions. Incorporating multimodal elements such as illustrations and audio-visual adaptations could also offer deeper insights into how various modes of communication contribute to meaning-making and ethical development in children’s literature.